(untitled) (Al-Academy, 2017)
Since his first existence on earth, human had formed a connecting link for a regressive, kinetic and developed relationship that comes from a semi-complicated interaction between natural environment and constructed environment, and this resulted in the survival of human and his existence continuance. Constructed environment enabled human to survive the natural environment inconstancies and enemies as predators, also it helped him to feel safe, comfortable and to practice his everyday life activities...etc. This alternative interaction resulted in creating a civilized legacy for a group of landmarks that tell about the development of this relationship by elemental output that reached us either by documents and manuscripts or as an existed landmark and by analyzing it we can realize the intellectual, cultural, scientific and social dimension of human during that era. The Baghdadi house is considered as one of these landmarks that tells about simplicity as a closed block from the outside and flexible complicated from the inside in a Pluralism gathering not in the number of spaces but in the multi-functionality of each space